Factors that May Influence the Performance of Wireless Sensor Networks - Mansouri, Majdi; Sardouk, Ahmad; Merghem-boulahia, Leila; Gaiti, Dominique; Snoussi, Hichem; Rahim-amoud, Rana; Richard, Cedric (IntechOpen, 2010)
None